Commodifying compassion: a critical discourse analysis of Spanish zoo, aquarium and animal theme parks’ lobbies - Aranceta-Reboredo, Olatz; Almiron, Núria (Frontiers in Communication, 2024)
The influence of the zoological park industry on public compassion remains an understudied area that is pivotal to understanding how public relations—specifically persuasive communication—attempts to shape public consent regarding the use of animals in entertainment. This paper addresses this issue by conducting a critical discourse analysis of the main interest groups in Spain’s zoological park industry: AIZA, Grupo Parques Reunidos, and Loro Parque Fundación. The results show that despite these actors’ compassionate self-representations, they use objectifying language, biological hierarchization, and commodification to represent nonhuman animals. In particular, they portray themselves as “advocates” for animal welfare and legitimize their efforts through a process akin to ethics washing. They use thematic elements and emotional engagement to convey the concept of the “modern zoo.” Finally, they strategically acknowledge societal compassion and frame themselves as aligned with current societal values and attitudes. We conclude that the current discursive strategies of the main Spanish zoological park industry lobbies go beyond the typical arguments related to entertainment, science and conservation, instrumentalizing public compassion to justify the captivity, confinement and exhibition of nonhumans.